Manual Counselling Supervision - Nor Mazlina, Ghazali (UNIMAS Publisher, 2025)
Manual Counselling Supervision offers a comprehensive guide to supporting counsellors through structured, theory-based, and reflective supervision. This manual explores the historical evolution of supervision, its purposes, and various types and styles used to tailor the experience to individual needs. It delves into theoretical frameworks and models such as System Approach to Supervision Model, Contextual Factors of Supervision, Discrimination Model of Supervision, and Developmental Model, providing practical tools for effective supervision interventions. Key themes include managing the roles and relationships between supervisors and supervisees, addressing multicultural considerations, and fostering professional development. Additionally, the manual emphasizes navigating legal and ethical challenges to ensure quality practice and safeguard both client and counsellor well-being